Legal nature of the proceedings and the decision to grant a scholarship for the PhD candidate in Polish law - Majewski, Kamil (Актуальні проблеми правознавства, 2018)
Legal nature of the proceedings and the decision to grant a scholarship for the PhD candidate in Polish law